1997
DOI: 10.1002/(sici)1097-0142(19970501)79:9<1828::aid-cncr28>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Proinflammatory cytokines, nutritional support, and the cachexia syndrome

Abstract: tients with both acute and chronic inflammation secondary to either cancer, Edward M. Copeland III, M.D.chronic infectious processes, surgical injury, trauma, or burns. For the patients who cannot support themselves by enteral feeding, total parenteral nutrition remains an Department of Surgery, University of Florida College of Medicine, Gainesville, Florida.essential tool to minimize nitrogen losses and replete the depleted patient. However, in patients with active inflammation, nitrogen retention and lean ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 163 publications
(33 citation statements)
references
References 92 publications
0
33
0
Order By: Relevance
“…As a result, when the rest-activity rhythm becomes disrupted, signals from the hypothalamus can prompt changes in the hypothalamic-pituitary-adrenal axis, ultimately activating the immune system, resulting in inflammation (Moldawer & Copeland, 1997). The release of pro-inflammatory cytokines and other growth factors hinders the coordination of cell metabolism and may lead to tumor cell hyperplasia (Moldawer & Copeland, 1997). Animal and clinical studies have shown that regular rest-activity rhythm enhances tolerance to anticancer drugs (Granda & Lévi, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…As a result, when the rest-activity rhythm becomes disrupted, signals from the hypothalamus can prompt changes in the hypothalamic-pituitary-adrenal axis, ultimately activating the immune system, resulting in inflammation (Moldawer & Copeland, 1997). The release of pro-inflammatory cytokines and other growth factors hinders the coordination of cell metabolism and may lead to tumor cell hyperplasia (Moldawer & Copeland, 1997). Animal and clinical studies have shown that regular rest-activity rhythm enhances tolerance to anticancer drugs (Granda & Lévi, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing evidence that constant activation of the innate immune system occurs in several chronic inflammatory processes, including RA 2. This persistent activation promotes constitutional changes, metabolic abnormalities and destruction and remodelling of tissues in persons with chronic, uncontrolled disease 9. Experiments have found that the administration of IL1 stresses host defences and mediates the response to disease.…”
Section: Role Of Il1mentioning
confidence: 99%
“…Cachexia is a chronic inflammatory syndrome that manifests predominantly as the progressive wasting of body fat and/or protein, and changes in energy balance that cannot be explained by anorexia alone, and is associated with an ongoing hepatic acute phase response, anemia, hyperlipidemia and presence of sickness syndromes (4). Clinically, cancer patients who develop cachexia are more susceptible to infection and sepsis (5).…”
Section: Introductionmentioning
confidence: 99%